Seasonal forecasting and health impact models: challenges and opportunities. Issue 1 (18th July 2016) - Ballester, Joan; Lowe, Rachel; Diggle, Peter J.; Rodó, Xavier
Abstract : After several decades of intensive research, steady improvements in understanding and modeling the climate system have led to the development of the first generation of operational health early warning systems in the era of climate services. These schemes are based on collaborations across scientific disciplines, bringing together real‐time climate and health data collection, state‐of‐the‐art seasonal climate predictions, epidemiological impact models based on historical data, and an understanding of end user and stakeholder needs. In this review, we discuss the challenges and opportunities of this complex, multidisciplinary collaboration, with a focus on the factors limiting seasonal forecasting as a source of predictability for climate impact models.